NEUTROPHIL-LYMPHOCYTE RATIO AT PRESENTATION IN SEVERE COVID-19 PNEUMONIA AND ITS EFFECTS ON CLINICAL OUTCOMES - Hanif, Mehak; Sumalani, Kamran Khan; Mandhan, Vishal; Shaikh, Zarkesh; Haider , Shahbaz (Infectious Diseases Journal of Pakistan, 2022)
Background: To determine the neutrophil-lymphocyte ratio (NLR) at presentation in hospitalized patients from Pakistan with severe COVID-19 pneumonia and assess its effect in predicting disease severity and clinical outcomes. Material and Methods: A cross-sectional study was carried out at the COVID isolation ward of a major tertiary care government hospital in Karachi, Pakistan. The study included 190 patients who were admitted within a 5-month timeframe from 1/2/2021 till 30/6/2021. Patient demographic information, comorbidities, clinical manifestations of COVID-19 infection and laboratory values at the time of presentation, including Hemoglobin, platelets, NLR, glomerular filtration rate, markers of inflammation, liver function tests, and electrolytes were documented. Patient outcomes and requirement for mechanical ventilation were evaluated 28 days post admission and compared to the NLR at presentation. Results: Mean NLR was 11.1. Mode and Median NLR were 8.6. The range of NLR was from 0.7 to 47.7. Mean NLR was higher in non-survivor’s compared to survivors (p-value 0.043) and higher in patients who required mechanical ventilation compared to those who did not (p-value 0.028). There was no significant variation observed between NLR and the length of hospital stay. Using the ROC curve, the best cut-off value to predict mortality was 8.550, with a sensitivity of 0.643 and specificity of 0.417 Conclusion: Patients with severe COVID-19 pneumonia frequently have high neutrophil-lymphocyte ratios at presentation, and this is linked to a higher in-hospital mortality rate and need for mechanical ventilation. Keywords: Neutrophil-lymphocyte ratio, COVID-19, Mortality rate, Mechanical ventilation